Law and morality: an evaluation of the role of religion in criminalization - Alili, Ngozi (African journal of law and criminology, 2015)
There exists a raging controversy as to the distinction between what is legally wrong and therefore a “crime” and what is morally wrong and therefore a “sin”. This discourse is therefore a spirited attempt at resolving conflicting views in this area of the law. It considered the role of the church and other religious schools of thought in the molding and the formulation of the criminal law in alliance with the codification of some forbidden human conducts which is a legislative function. It was observed that criminal laws reflect the moral and ethical beliefs of the society. Murder for instance, is forbidden not only by the criminal law, the violation of which attracts earthly sanction or punishment, but also by the moral law, the violation of which attracts eternal sanction or punishment in the hereafter. The significance of “moral law” lies in the fact that it compels most people in the society to conform to the standards necessary for public order regardless of whether a police man is watching or not. The significance extends to the fact or discovery that the old English judges were much attuned to the moral sentiments of their communities on the basis of which criminal laws were enacted against adultery, rape, murder, stealing, arson etc. and this historical foundation justifies the definition of a “crime” as a “moral wrong”. It was concluded that though all criminally wrongful acts are also morally wrongful, not all morally wrongful acts are criminally wrongful and the marriage between the criminal law which is purely a legislative creation and moral laws which operate within religious realms, rather than their divorce, is good for the health of the society.